Pindolol Rescues Anxiety-Like Behavior and Neurogenic Maladaptations of Long-Term Binge Alcohol Intake in Mice - Patkar, Omkar L.; Belmer, Arnauld; Beecher, Kate; Jacques, Angela; Bartlett, Selena E. (Frontiers in Behavioral Neuroscience, 2019)
Long-term binge alcohol consumption alters the signaling of numerous neurotransmitters in the brain including noradrenaline (NE) and serotonin (5-HT). Alterations in the signaling of these neuronal pathways results in dysfunctional emotional states like anxiety and depression which are typically seen during alcohol withdrawal. Interestingly, studies have demonstrated that development of alcohol-induced negative affective states are linked to disrupted neurogenesis in the dentate gyrus region of the hippocampus in alcohol dependent animals. We have previously shown that modulation of NE and 5-HT activity by pharmacological targeting of β-adrenoreceptors (β-ARs) and 5-HT1A/1B receptors with pindolol reduces consumption in long-term alcohol consuming mice. Since these receptors are also involved in emotional homeostasis and hippocampal neurogenesis, we investigated the effects of pindolol administration on emotional and neurogenic deficits in mice consuming long-term alcohol (18 weeks). We report that acute administration of pindolol (32 mg/kg) reduces anxiety-like behavior in mice at 24 h withdrawal in the marble burying test (MBT) and the elevated plus maze (EPM). We also show that chronic (2 weeks) pindolol treatment (32 mg/kg/day) attenuates alcohol-induced impairments in density of immature neurons (DCX+) but not newborn cells (BrdU+). Pindolol treatment rescued alcohol-induced impairments in the differentiation of newborn proliferating cells (BrdU+, Ki67+, DCX-) into newborn immature neurons (BrdU+, Ki67±, DCX+). These results suggest that pindolol, through its unique pharmacology may rescue some but not all deficits of long-term alcohol abuse on the brain and add further value to the properties of pindolol as a strong pharmaceutical option for alcohol use disorders (AUDs).